(3hUGjG GdEeGe jMji Hf MeRI GdYdhi hYghOg GdJi YgO HgG Edi ChdGOgs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3faYfG Gddg HgG hQRbfG GdYed HeG ajgG , hgj CQHY , GdChdi hgj GddHGH ai eMGSf GdBOGH s
(3BNQgG (B:s
(3hGdMeO ddg Ydi cd MGd ef GdCMhGd , hGdEYJeGO Ydi QH GdYHGO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG JUMjMGJs
(3HChdgG SeGYs
(3GdfSNI ebGHdI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJhMjO hGdedd hGdfMds